Job Insecurity and Work Environment: How Job Satisfaction Affects Performance at PT Chang Jui Fang Indonesia - Bunga Rosliana; Dwie Afriyanto; Anna Suzana (Green Publisher Indonesia, 2025)
In the competitive era of globalization, employee performance plays a crucial role in maintaining the sustainability and productivity of a company. This study aims to analyze the effect of job insecurity and work environment on employee performance, with job satisfaction as a mediating variable at PT Chang Jui Fang Indonesia. The issue arises from a decline in employee performance achievements, which are suspected to be influenced by job insecurity and suboptimal work environment conditions. This research uses a quantitative approach with a survey method by distributing questionnaires to 326 production employees, selected using simple random sampling. Data analysis is performed using Structural Equation Modeling with Partial Least Square (SEM-PLS) approach through SmartPLS 4 software. The independent variables in this study are job insecurity (X1) and work environment (X2), the mediating variable is job satisfaction (Z), and the dependent variable is employee performance (Y). The results of the study show that job insecurity negatively and significantly affects job satisfaction and performance. On the other hand, the work environment positively and significantly affects job satisfaction and performance. Furthermore, job satisfaction was found to have a positive and significant effect on employee performance. The analysis of indirect effects indicates that job satisfaction significantly mediates the effect of job insecurity and work environment on performance. Thus, companies need to pay attention to psychological factors, particularly in reducing job insecurity and creating a conducive work environment to improve job satisfaction and ultimately lead to better employee performance.